2015
DOI: 10.1167/15.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial compression: Dissociable effects at the time of saccades and blinks

Abstract: Various studies have identified systematic errors, such as spatial compression, when observers report the locations of objects displayed around the time of saccades. Localization errors also occur when holding spatial representations in visual working memory. Such errors, however, have not been examined in the context of eye blinks. In this study, we examined the effects of blinks and saccades when observers reproduced the locations of a set of briefly presented, randomly placed discs. Performance was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The mislocalization toward the saccade target location at saccade onset is consistent with the typical pattern of perisaccadic compression Ross et al, 1997;Lappe et al, 2000;Kaiser & Lappe, 2002;Ostendorf et al, 2007). The preceding mislocalization toward the fixation location is consis- tent with localization errors toward the initial fixation point described by Haladjian et al (2015) for double overlap saccades. Since this mislocalization occurred for single overlap saccades, it is not reliant on the presence of a return saccade.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The mislocalization toward the saccade target location at saccade onset is consistent with the typical pattern of perisaccadic compression Ross et al, 1997;Lappe et al, 2000;Kaiser & Lappe, 2002;Ostendorf et al, 2007). The preceding mislocalization toward the fixation location is consis- tent with localization errors toward the initial fixation point described by Haladjian et al (2015) for double overlap saccades. Since this mislocalization occurred for single overlap saccades, it is not reliant on the presence of a return saccade.…”
Section: Resultssupporting
confidence: 79%
“…This mislocalization begins about 150 ms before the saccade and peaks between 100 and 50 ms before saccade onset. Haladjian et al (2015) first reported evidence for compression toward fixation in a study involving a sequence of first outward and then return saccades. In that study, the fixation marker was also the target of the return saccade so that the compression might have been driven by the preplanning of the return saccade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This takes us to the last step of image processing: the calculation of a noisy image, that is to be analyzed by the cortical recognition process. As with all biological organs, the visual system also has some temporal uncertainty 16,17 , which is usually modeled at one instant as additive noise:…”
Section: Methodsmentioning
confidence: 99%
“…The “optically filtered” retinal image can be reconstructed from the monochromatic aberrations of the human eye 1114 , which is measurable using Shack-Hartmann wavefront sensors 15 . As a next step, neural transfer simulates the post-retinal neural image, with additional neural noise being taken into account to determine the noisy image which is finally recognized by the visual cortex 16,17 . The recognition process is usually represented as a template-matching algorithm, which is known to be one of the simplest and oldest models of pattern vision 18–20 .…”
Section: Introductionmentioning
confidence: 99%